Chatbots as Classroom Assistants: A Qualitative Study on Teachers’ Perspectives - Mashinchi, Ali Asghar (AI and Tech in Behavioral and Social Sciences, 2024)
This study aims to explore teachers’ perspectives on the integration of chatbots as classroom assistants, focusing on identifying the perceived benefits, challenges, and the broader implications of chatbot use in educational settings. It seeks to contribute to the understanding of how chatbots can be effectively integrated into teaching and learning processes, and what factors influence their acceptance and utility from the viewpoint of educators. A qualitative research design was employed, utilizing semi-structured interviews with 22 teachers who have experience with or interest in using technology in their teaching practices. Participants were selected from a range of educational levels and disciplines to ensure diverse perspectives. The interviews were transcribed verbatim, and thematic analysis was conducted to identify recurring themes and concepts related to the use of chatbots in education. The analysis revealed five main themes: Perceived Benefits, Challenges and Concerns, Implementation Strategies, Technological Integration, and Teacher and Student Roles. Perceived benefits included enhanced student engagement, administrative efficiency, and pedagogical support. Challenges and concerns encompassed technical issues, pedagogical effectiveness, and emotional and social impacts. Implementation strategies highlighted the importance of curriculum integration, professional development, and technical support. The role of technological integration was discussed in terms of enhanced learning tools, while teacher and student roles focused on evolving educational dynamics and autonomy. The study concludes that while chatbots hold significant potential to enhance educational experiences, their integration into classrooms must be navigated with an understanding of the associated challenges and concerns. Effective implementation requires addressing technical reliability, ensuring pedagogical soundness, and considering the emotional and social implications of technology-mediated education. The study underscores the importance of a collaborative approach to chatbot integration, involving educators, students, and developers, to maximize the educational benefits of this technology.